Ages and glass compositions for paired large-volume eruptions from the Acigöl volcanic complex, Cappadocia (Turkey) - Atıcı, Gokhan; Schmitt, Axel Karl; Friedrichs, Bjarne; Sparks, Stephen; Danišík, Martin; Yurteri, Esra; Gündoğdu, Evren Atakay; Schindlbeck, Julie Christin; Çobankaya, Mehmet; Wang, Kuo-Lung; Lee, Hao-Yang (Mediterranean geoscience reviews, 2019)
Acigöl volcanic complex is a bimodal volcanic field located at the western margin of the Neogene-Quaternary Cappadocian volcanic province in Central Anatolia (Turkey). Its most voluminous eruptions are preserved as a pair of widespread tuffs known as Lower Acigöl Tuff (LAT) and Upper Acigöl Tuff (UAT). Both are nearly aphyric high-silica rhyolites that are compositionally identical; they can be distinguished, however, by the presence of obsidian lithics in UAT and the absence thereof in LAT. Here, we report the discovery of medial deposits of these tuffs at ~ 60-65 km distance from their source, and re-estimate the volume for LAT in the range of 21.4-26.7 km3 (similar constraints are lacking for UAT, but a subequal volume is assumed). Development of paleosol between LAT and UAT provides evidence for a hiatus between both events which is further supported by radiometric dating using combined U-Th and (U-Th)/He zircon geochronology. The revised age for LAT based on sequence modeling of U-Th zircon crystallization and (U-Th)/He zircon eruption ages is 190 ± 11 ka, whereas new and published (U-Th)/He zircon ages indicate eruption of UAT at 164 ± 4 ka (uncertainties generally stated at 1σ). The compositional similarity between both eruptions previously known from whole-rock analyses also extends to glass major, minor, and trace element compositions. Moreover, U-Th zircon crystallization ages are also indistinguishable between LAT and UAT in proximal and medial locations. U-Pb zircon ages for crystals in secular equilibrium indicate a provenance from Cretaceous granitic basement and Miocene volcanic overburden typical for Cappadocia, and such xenocrysts appear to be slightly more common in LAT compared to UAT. The compositional similarity between LAT and UAT along with the apparent recycling of zircon from the non-erupted LAT magma during the UAT event indicates sequential tapping of rhyolite melt from a magma system that maintained thermal and compositional uniformity over a protracted time interval. This can be explained by rhyolite melt extraction from a thermally buffered crystal mush that remained viable to produce voluminous high-silica eruptions for few 10s of ka. The subsequent migration of eruptive activity in the Acigöl volcanic complex from east to west also led to a change in magma chemistry and triggered a new pulse of zircon crystallization, indicating abandonment of the previous magmatic focus, and a shift of magma input to a new location. The identification of sizable medial deposits of LAT and UAT implies that both tephra units are potentially useful marker horizons for marine isotope stage (MIS) 6 sedimentary sequences in and around Anatolia. The recent discovery of UAT in a Black Sea sediment core supports this view.